A study on the factors that influence job satisfaction among the employees of insurance companies in Alor Setar, Kedah - Nor Shazween, Nizamuddin (2014)
This study is to examine and focus on the understanding of factors that influence job satisfaction among employees of insurance companies mainly in Alor Setar, Kedah. Data were collected from few insurance companies around Alor Setar, Kedah which are Prudential Assurance Malaysia Berhad, Allianz Malaysia Berhad, Multi-Purpose Insurance Berhad, Tokio Marine Insurance (Malaysia) Berhad, Lonpac Insurance Berhad, Great Eastern Life Assurance (M) Berhad, ING Insurance Berhad, American International Assurance Berhad, Takaful Ikhlas Berhad, Etiqa Insurance Berhad, MCIS Zurich Insurance Berhad, ACE Jerneh Insurance Berhad, Uni Asia Insurance Berhad, Syarikat Takaful Malaysia Berhad, MSIG Insurance (M) Berhad and Manulife Insurance (M) Berhad. The study involved 102 respondents who are employed at various insurance companies around Alor Setar, Kedah. The questionnaire is developed to analyze using “Statistical Package for Social Science” version 21.0 (SPSS 21.0). The research will undergo analysis such as Reliability Test which is Cronbach‟s Alpha, Pearson Correlation and also Multiple Regression. The main purpose is to determine the relationship between the independent variables and dependent variable. The independent variables in the study are as follows which are salary, leadership, career advancement and job stress, while the dependent variable of the study is job satisfaction. Among the independent variables, salary was found to be the dominant dimension in influencing the job satisfaction among the employees in the insurance companies. In addition, out of four variables, three of them give significant results which are salary, leadership and career advancement while job stress gives insignificant result. Therefore, the management should be concerned on those three factors as key motivators towards satisfying the employees in insurance companies. This paper will benefit the insurance companies to compete well and drive towards sustainable growth. As a result of this research, the insurance companies will have a clear picture of their employees in term of what actually satisfied their employees in doing their job well.